2010
DOI: 10.1007/978-94-007-0265-3_32
|View full text |Cite
|
Sign up to set email alerts
|

TRP Channels and Neural Persistent Activity

Abstract: One of the integrative properties of the nervous system is its capability to, by transient motor commands or brief sensory stimuli, evoke persistent neuronal changes, mainly as a sustained, tonic action potential firing. This neural activity, named persistent activity, is found in a good number of brain regions and is thought to be a neural substrate for short-term storage and accumulation of sensory or motor information [1]. Examples of this persistent neural activity have been reported in prefrontal [2] and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 143 publications
1
43
0
Order By: Relevance
“…Pharmacological activation of some metabotropic cholinergic receptors, which activates CAN currents, induces persistent neural activity in the prefrontal cortex 21 , the hippocampus 22 , the entorhinal cortex 23 and the lateral amygdala 24 . Canonical transient receptor potential channels (TRPCs) have been proposed to underlie some CAN currents [25][26][27] . The lamprey reticulospinal neurons sustain action potential firing after a brief tap on the snout, which induces an escape response; the sustained neural activity requires CAN currents activated by the NMDA receptors 15,28 .…”
mentioning
confidence: 99%
“…Pharmacological activation of some metabotropic cholinergic receptors, which activates CAN currents, induces persistent neural activity in the prefrontal cortex 21 , the hippocampus 22 , the entorhinal cortex 23 and the lateral amygdala 24 . Canonical transient receptor potential channels (TRPCs) have been proposed to underlie some CAN currents [25][26][27] . The lamprey reticulospinal neurons sustain action potential firing after a brief tap on the snout, which induces an escape response; the sustained neural activity requires CAN currents activated by the NMDA receptors 15,28 .…”
mentioning
confidence: 99%
“…Although the molecular identity of the ion channel mediating this response is unknown, it appears to be gated by Ca 2+ (or Ca 2+ ions bound to an accessory protein), is permeable to Na + and Ca 2+ , and is sensitive to flufenamic acid (FFA; Haj-Dahmane & Andrade 1999, Lei et al 2014, Rahman & Berger 2011, Tahvildari et al 2008, Zhang et al 2011), a nonsteroidal anti-inflammatory agent. Several groups have hypothesized that a subtype of transient receptor potential (TRP) channels may mediate I CAN responses, based on pharmacological studies (Lei et al 2014, Reboreda et al 2011, Petersson & Fransén 2012) and tests of peptides that interfere with TRP channel function (Yan et al 2009, Zhang et al 2011). However, thus far no direct evidence has demonstrated that persistent firing and the associated afterdepolarization response are abolished in TRP channel knockout animals [although Lei et al (2014) found partial blockade in TRPM5 knockout mice].…”
Section: Cell-autonomous Biophysical Mechanisms For Generating Persismentioning
confidence: 99%
“…However, thus far no direct evidence has demonstrated that persistent firing and the associated afterdepolarization response are abolished in TRP channel knockout animals [although Lei et al (2014) found partial blockade in TRPM5 knockout mice]. Given the wide diversity of TRP channels (Reboreda et al 2011), fully testing this hypothesis may require generating mice that are null for many different TRP subunits.…”
Section: Cell-autonomous Biophysical Mechanisms For Generating Persismentioning
confidence: 99%
“…Ca 2+ also acts as a ubiquitous secondary messenger to modulate neuronal functions and also plays an important role in the relay of information via membrane depolarization [4,49,50]. TRPCs are predominantly expressed in neuronal cells and, thus, could be prime contributors in regulating fundamental neuronal functions via regulating the Ca 2+ flux in these neuronal cells [50].…”
Section: Physiological Function Of Trpcs In Neuronal Cellsmentioning
confidence: 99%
“…Too much or too little Ca 2+ can be deadly to these neurons, so the Ca 2+ levels are carefully controlled in and outside of the cell. Such disturbances in Ca 2+ homeostasis have been involved in neurodegenerative diseases, such as Parkinson’s, Alzheimer’s and Huntington’s [2,3], which is mainly due to the high dependence of Ca 2+ signaling in various neuronal cells essential for their function [4]. Ca 2+ mobilization in neuronal cells is tightly regulated by different Ca 2+ channels and pumps in the plasma membrane and in the organelle membranes.…”
Section: Introductionmentioning
confidence: 99%